Trade Networks, Heroin Markets, and the Labor Market Outcomes of Vietnam Veterans - Jakub Lonsky; Isabel Ruiz; Carlos Vargas-Silva (Global Labor Organization (GLO), 2021)
The role of ethnic immigrant networks in facilitating international trade is a well-established phenomenon in the literature. However, it is less clear whether this relationship extends to illegal trade and unauthorized immigrants. In this paper, we tackle this question by focusing on the case of the heroin trade and unauthorized Chinese immigrants in the early 1990s United States. Between mid-1980s and mid-1990s, Southeast Asia became the dominant source of heroin in the US. Heroin from this region was trafficked into the US by Chinese organized criminals, whose presence across the country can be approximated by the location of unauthorized Chinese immigrants. Instrumenting for the unauthorized Chinese immigrant enclaves in 1990 with their 1900 counterpart, we first show that Chinese presence in a community led to a sizeable increase in local opiates-related arrests, a proxy for local heroin markets. This effect is driven by arrests for sale/manufacturing of the drugs. Next, we examine the consequences of Chinese-trafficked heroin by looking at its impact on US Vietnam-era veterans - a group particularly vulnerable to heroin addiction in the early 1990s. Using a triple-difference estimation, we find mostly small but statistically significant detrimental effects on labor market outcomes of Vietnam veterans residing in unauthorized Chinese enclaves in 1990.
Keywords: F16; F22; J15; K42; 330; Trade networks; heroin markets; Vietnam veterans; labor market outcomes